2022
DOI: 10.3389/fpubh.2022.892756
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Multiple High-Powered Magnetic Buckyballs Ingestion—Experience From Six Tertiary Medical Centers

Abstract: Multiple high-powered magnetic Buckyball ingestions may lead to a high risk of severe complications. Great concerns have been raised by public health workers, and it remains challenging for clinicians to solve this troublesome problem. We report a large case series of children with Buckyball ingestion from six tertiary medical centers. The clinical data, including demographics, medical history, diagnosis tools, management options, intraoperative or endoscopic findings, and outcomes, were retrospectively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“… 1 Nonetheless, its diagnostic precision is dependable upon the expertise and experience of the physician. 15 CT imaging has the capability to identify intestinal obstruction, perforation, abdominal inflammation, and other associated complications. However, the contentious aspect surrounding CT employment in the diagnosis of digestive tract foreign bodies stems from its considerable cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 Nonetheless, its diagnostic precision is dependable upon the expertise and experience of the physician. 15 CT imaging has the capability to identify intestinal obstruction, perforation, abdominal inflammation, and other associated complications. However, the contentious aspect surrounding CT employment in the diagnosis of digestive tract foreign bodies stems from its considerable cost.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Such surgical procedures predominantly encompass laparoscopic surgery and laparotomy. 15 , 16 The former is the traditional surgical approach, suitable for all gastrointestinal foreign bodies. The latter, as indicated by Cai DT et al, can be employed for managing patients who have ingested foreign bodies for more than 2 weeks and exhibit milder clinical symptoms and signs, with the foreign body located in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both patients had histories of prolonged observation of not moving magnets, low-dose CTs were performed to exclude extra lumen location of objects or further damage to surrounding organs. Ultrasound is a safe and accurate noninvasive modality used to determine the magnet location [ 6 ]. However, those examinations were inconclusive in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Intervals between the ingestion of each magnet may result in locating them in different segments of the intestine. As the ingestion regards high-power magnets, their attractive forces can lead them to merge even through several bowel loops, causing perforations, necrosis, or fistulas [ 6 ]. Hussain et al observed gastric ulceration during the endoscopic removal of multiple magnets less than 8 hours after swallowing, emphasizing the harmful effects on the upper GI tract [ 14 ].…”
Section: Discussionmentioning
confidence: 99%